(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2021)
Introduction: Meningitis is an inflammatory process capable of affecting the central nervous system in humans; thus, it is a global public health issue. Objectives: Describing meningitis epidemiology in Paraná State, Brazil, as well as the impact of introducing conjugate vaccines (pneumococcal and meningococcal) in the immunization schedule. Methods: Retrospective, observational and descriptive study about notified and confirmed meningitis cases in Paraná State. Data were organized in pre- (2007 to 2009) and post-introduction (2010 to 2016) of meningococcal C and 10-valent pneumococcal vaccines. Results: In total, 17,045 meningitis cases were confirmed in Paraná State from 2007 to 2016 - 2007 was the year recording the largest number of cases (n=3,489). Most notified cases were diagnosed in men (59.1%) and mostly affected patients in the age group 0-to-9-years. Aseptic meningitis (viral) was the most often diagnosed type of the disease among meningitis with known etiology; it was followed by Neisseria meningitidis, Streptococcus pneumoniae, Mycobacterium tuberculosis and Haemophilus influenzae. Neisseria meningitidis serogroup C was the most common type; it was followed by serogroup B. There was significant decrease in the frequency of N. meningitidis and S. pneumoniae in 1-to-4-year-old children, after vaccination. Conclusion: Vaccine-preventable bacterial meningitis rate has decreased in Paraná State, mainly due to the introductionof conjugate vaccines. Understanding meningitis etiology is a key factor to measuments taken by epidemiological surveillance to prevent and control the diseaseand, consequently, to help improving public health.